A functional modified graphene oxide/nanodiamond/nano zinc oxide composite for excellent vulcanization properties of natural rubber. Issue 68 (17th November 2020) - Yang, Zhen; Huang, Yan; Xiong, Yuzhu
Abstract : A modified graphene oxide/nanodiamond/nanozinc oxide (MGO/ND/nanoZnO) functional hybrid filler is designed and prepared to improve the vulcanization efficiency of a rubber composite and to reduce the use of ZnO. Abstract : A modified graphene oxide/nanodiamond/nanozinc oxide (MGO/ND/nanoZnO) functional hybrid filler is designed and prepared to improve the vulcanization efficiency of a rubber composite and to reduce the use of ZnO. ND was grafted onto graphite oxide with the aid of 4, 4′-methylene diphenyl diisocyanate (MDI). NanoZnO, with high surface activity, was then loaded onto the MGO/ND complex through the wet chemical method, in order to synthesize the MGO/ND/nanoZnO functional hybrid filler. Rubber composites were prepared using the rubber latex composite method and their vulcanization behaviors were investigated. Our results show that the MGO/ND/nanoZnO functional hybrid filler can remarkably improve the vulcanization behaviors of the rubber composite. Compared with that of pure natural rubber (NR), the vulcanization activation energy of the rubber composite was reduced by approximately 16%. Moreover, the vulcanization efficiency can be improved by 63% ( i.e., the optimum cure time is shortened from the original 405 s to 150 s) after the same amount of traditional ZnO was replaced by the functional hybrid filler loaded with 1 wt% nanoZnO. The prepared MGO/ND/nanoZnO functional hybrid filler thus provides a promising alternative to improve the vulcanization efficiency of rubber composites.